Trade-Offs Between Patient Experience and Health Care Access - Michelle S. Wong; W. Neil Steers; Kimberly E. Lind; Donna L. Washington (Medical Care, 2026)
Background: Racial and ethnic disparities in patient-reported experiences exist in the Veterans Health Administration (VA) and in VA-paid health care from non-VA providers (“community care”), but how these disparities compare is unknown. Objectives: We compared racial and ethnic disparities in patient-reported experiences between VA primary care and community care, and calculated differences in VA versus community care by patient race and ethnicity. Methods: Using cross-sectional data from the 2020 to 2023 VA Survey of Healthcare Experiences of Patients—VA Primary Care and Community Care surveys, we used linear and logistic regressions to assess patient-reported access, care coordination, communication, and provider satisfaction for each racial and ethnic group by setting, and calculated differences-in-differences by race and ethnicity and setting. Results: Primary care provided in community care had larger racial and ethnic disparities in patient-reported experiences of care than VA. Compared with White Veterans, age and sex-adjusted community care disparities exceeded VA disparities for communication among Black Veterans by 13 percentage points; care coordination for American Indian/Alaska Native, Black, and multirace Veterans by 22, 12, and 16 percentage points, respectively; and provider satisfaction for American Indian/Alaska Native Veterans by 34 percentage points. Conclusion: Our findings highlight potential unintended consequences of VA’s efforts to improve timely access by increasing reliance on community care, which may inadvertently widen disparities and contribute to worse care experiences. We suggest several policy implications, including tailoring existing patient tools to navigate community care to minoritized groups experiencing disparities, and providing VA and CC metrics to Veterans to support informed decisions.